Manejo de pastagem natural em pastoreio rotativo no período de outono/inverno - Kuinchtner, Bruno Castro (2013)
The aim of this study was to evaluate the performance, the ingestive behavior and dry matter intake of beef heifers receiving supplementation on natural pasture grazed in two thermal sums, which defined the interval of rest between grazing during autumn-winter season. A complete randomized block design experiment with two treatments and three replications was conducted from May to September 2011 in an experiment area of theUniversidadeFederal de Santa Maria, located at Depressão Central region, in Rio Grande do Sul state, Brazil. The treatments were two thermal sums: 375 and 750 degrees-days (DD) determined by the intervals between rotational grazing periods, the 375 DD treatment favors prostrate species(Axonopusaffinis e Paspalumnotatum) and the 750 DD treatment favors tussock species(Aristidalaevis e Saccharumangustifolius). The 23ha experimental area was divided into six experimental units, which housed two treatments and three replications. A total of 36 beef heifers with an average age of 18 months each, 18 Angus heifers with an average initial weight of 212 ± 19kg and 18 Charolais × Nellore crossbreed heifers with average initial weight of 227 ± 9.9 kg.Throughout the experiment all heifers received a ground corn supplement at a rate of 0.5% of body weight daily at 2:00 p.m. and had free access to mineral supplementation protein (45% CP). The use of functional groups morphogenic traits to determine the rest intervals of the paddocks in the rotational grazing method results in better pasture quality and high stocking rate Maintain at least 30% of leaf blade avoids discomfort in behavior activities and average height of at least 10cm of lower strata in natural pastures avoids reduction in intake in grazing beef heifers.